(untitled) (Interdisciplinary Studies Journal, 2026)
This research aimed to investigate Brazilian scientific production on Education of Ethnic-Racial Relations. To this end, a state-of-the-art research was conducted, with works selected from 2011 to 2018, through consultation in the databases of the Brazilian Digital Library of Theses and Dissertations (BDTD). Eight dissertations were selected and analyzed in this bibliographic survey. Among the results found, we highlight that the selected works were from different regions of the country, which demonstrates that the difficulty of implementing and enforcing Law No. 10.639/2003 is not a difficulty of just one region of our country, but rather a problem that affects the entire Brazilian nation. It was found that most of the works were of a qualitative nature. It was found that, after twenty years of enactment of Law No. 10.639/2003, there are great advances, as well as great difficulties in its implementation, with Teacher Training being the great driving force for the theme of Education of Ethnic-Racial Relations to be recognized and developed effectively in Brazilian schools.